2011
DOI: 10.1501/vetfak_0000002448
|View full text |Cite
|
Sign up to set email alerts
|

Pathological findings of experimental Aeromonas hydrophila infection in Nile tilapia (Oreochromis niloticus)

Abstract: Summary:In this study, clinical findings with macroscopic and microscopic pathologic changes of the tissues and organs after necropsy examination at the 1 st , 2 nd , 3 rd , 5 th and 7 th days following intraperitoneally injection of Nile tilapia (Oreochromis niloticus) with Aeromonas hydrophila was aimed to be observed. Clinically; weakness, anorexia, swimming closer to surface, darkness in color with hyperemia and lysis of the fins were observed. In the macroscopic examination the liver was seen to be yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(12 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…The source of the hemorrhages throughout the body could be the hemolysin produced by the Aeromonas retrieved bacteria, which hemolyzes red blood cells (RBCs), in addition to the elastase enzyme, which significantly contributes to vascular injury because the blood arteries are primarily made up of elastic and collagenous fibers. The clinical symptoms seen in this study almost the same as those identified by previously ( Ahmed and Shoreit, 2001 ; El-Ashram, 2002 ; Pretto-Giordano et al , 2010 ; Yardimci and Aydin, 2011 ; Noor El-Deen et al , 2014 ; Soliman et al , 2014 ; Othman et al , 2015 ; Dar et al , 2016 ; Omar et al , 2016 ; Abd El-Tawab et al , 2017 ; El-Barbary, 2017 ; Laith et al , 2017 ; Osman et al , 2017 ; Pech et al , 2017 ; Saleh et al , 2017 ; Amrullah et al , 2018 ; Khalil and Emeash, 2018 ; Hamouda et al , 2019 ; Hassan et al , 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…The source of the hemorrhages throughout the body could be the hemolysin produced by the Aeromonas retrieved bacteria, which hemolyzes red blood cells (RBCs), in addition to the elastase enzyme, which significantly contributes to vascular injury because the blood arteries are primarily made up of elastic and collagenous fibers. The clinical symptoms seen in this study almost the same as those identified by previously ( Ahmed and Shoreit, 2001 ; El-Ashram, 2002 ; Pretto-Giordano et al , 2010 ; Yardimci and Aydin, 2011 ; Noor El-Deen et al , 2014 ; Soliman et al , 2014 ; Othman et al , 2015 ; Dar et al , 2016 ; Omar et al , 2016 ; Abd El-Tawab et al , 2017 ; El-Barbary, 2017 ; Laith et al , 2017 ; Osman et al , 2017 ; Pech et al , 2017 ; Saleh et al , 2017 ; Amrullah et al , 2018 ; Khalil and Emeash, 2018 ; Hamouda et al , 2019 ; Hassan et al , 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…According to Soto [28] it is proven that bacteria are the cause of epithelial hyperplasia in gills, splenomegaly, renomegaly and necrosis in internal organs, mainly in spleen, heart, liver, kidney, brain and musculature. For example Yardimci, et al [29][30][31] indicate that species Aeromonas hydrophila is associated with hemorrhages in gills and skin, weakness and anorexia, as well as vision loss by breaking' orbital eyes, the above agrees with those reported by Clavijo et al [32], who reported that the presence of genus Edwardsiella sp., causes septicemia in internal and external organs, including kidney, liver and spleen, skin, rectum, fins, abdominal inflammation, and opaque eyes. Some pathogens are transmitted horizontally as indicated by Mauel et al [33], who pointed out that bacteria use water as a precursor vehicle, causing fish-to-fish outbreaks by direct contact.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, the provision of a good diet appears to be an important factor for the maintenance of cellular homeostasis and histoarchitecture in fish [114]. Similar pathological changes were reported in the Nile tilapia infected with A. hydrophila [115] and Japanese flounder (Paralichthys olivaceus) fish infected with Edwardsiella tarda [116]. Moreover, Ostaszewska et al [117] demonstrated a restoration in the hepatocyte architecture of silver bream (Vimba vimba) fish supplemented with natural feed additives.…”
Section: Discussionmentioning
confidence: 74%